GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA PUSKESMAS KOTA LHOKSEUMAWE - Nasution, Muhammad Alwi; Mauliza, Mauliza; Putri , Baluqia Iskandar; Wahyuni , Sri; Fonna, Tischa Rahayu (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
The upper and lower respiratory tracts can be affected by infectious diseases such as ARI. The child’s ability to recover is greatly influenced by the mother’s level of knowledge about respiratory diseases. The purpose of this study was to determine the description of mothers’ knowledge about ARI in the working area of ​​the Lhokseumawe City Health Center. This study used a cross-sectional approach and descriptive methodology. A total of 105 respondents followed the sampling procedure using Cluster Random Sample. The questionnaire used to collect data consisted of 20 statements. The results of the study showed that most mothers had high knowledge about ARI (89.5%), while 8.6% had sufficient knowledge, and 1.9% had poor understanding. The results of this study indicate that most mothers in this survey had sufficient knowledge, with the largest age group in the range of 26-35 years.